2012
DOI: 10.5565/rev/ec/v31n2.767
|View full text |Cite
|
Sign up to set email alerts
|

El problema de la producción y el consumo de energía: ¿Cómo es tratado en los libros de texto de educación secundaria?

Abstract: RESUMEN: En este trabajo indagamos sobre la atención que se presta al problema de la energía, en especial a los aspectos controvertidos de este, en una selección de libros de texto de la educación secundaria obligatoria. El estudio se ha centrado en los contenidos declarativos, que han sido categorizados. Se ha realizado un análisis detallado de las categorías relacionadas con los «pros y los contras de las actividades de producción» y «las implicaciones derivadas del consumo energético». Los resultados ponen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These authors concluded that important aspects such as the environmental impact related to this subject are ignored. On the other hand, other researchers [17] have shown that the attention and space given to non-renewable energies is greater than that given to renewable energies and conclude that the texts emphasize the traditional rather than the future possibilities. Likewise, these authors indicate that the attention paid by the curriculum to the subject of energy does not correspond to that given in the texts analyzed and, therefore, it is necessary to resort to the context of the real problems that humanity currently faces in this regard.…”
Section: Introductionmentioning
confidence: 97%
“…These authors concluded that important aspects such as the environmental impact related to this subject are ignored. On the other hand, other researchers [17] have shown that the attention and space given to non-renewable energies is greater than that given to renewable energies and conclude that the texts emphasize the traditional rather than the future possibilities. Likewise, these authors indicate that the attention paid by the curriculum to the subject of energy does not correspond to that given in the texts analyzed and, therefore, it is necessary to resort to the context of the real problems that humanity currently faces in this regard.…”
Section: Introductionmentioning
confidence: 97%